Coping Styles and Self-Care Behaviors among Diabetic Patients - Hamadzadeh S; Ezatti ZH; Abedsaeidi ZH; Nasiri N (Iran University of Medical Sciences, 2013)
Background ;Aims: Afflict by diabetes and patient's commitment for self-care, induces much stress in routine life which requires the use of coping styles for adaption. The aim of this study was to determine correlation between coping styles and self-care behaviors among diabetic patients.   Material ;Methods: In this descriptive-correlational study, 275 type 1 and2 diabetic patients were selected by convenience sampling from Taleghani hospital in Tehran. Data was collected by " Summary of Diabetes Self-care Activity Measure" and "Jalowice Coping Scale" and analyzed by descriptive and inferential statistics using SPSS-PC (v.16).   Results: The findings showed that there has been a positive significant correlation between Confrontive (r=0.28, p<0.05), Optimistic(r=0.28, p<0.01), Supportant (r=0.31,p<0.01)and Self-reliant (r=0 . 25,p<./01) coping styles and self-care behaviors. Moreover, there was negative correlation between Emotive (r= - 0.18, p<0.05) and Evasive (r= - 0.34, p<0.01) coping styles and self-care behaviors. There was also a significant correlation between total self-care behaviors and coping styles(r=0.26, p=0.018).  Conclusion: According to the findings, clinical staff especially nurses can improve the self-care and adaption among diabetic patients by encouraging them to apply effective coping methods.  Received: 18 Feb 2013   Accepted: 17 May 2013